Behavioral, energetic, and color trait integration in male guppies: testing the melanocortin hypothesis. (3rd July 2019) - Santostefano, Francesca; Fanson, Kerry V; Endler, John A; Biro, Peter A
Abstract: Individuals of the same population differ consistently from each other in the average expression of behavioral and physiological traits. Often, such traits are integrated and thus correlated with each other. However, the underlying proximate mechanisms generating and maintaining this among-individual covariation are still poorly understood. The melanocortin hypothesis suggests that the melanocortin pathways can have pleiotropic effects linking the expression of melanin-based coloration with physiological and behavioral traits. In the present study, we test this hypothesis in adult male guppies ( Poecilia reticulata ), by estimating among individual correlations between behaviors (activity, feeding, boldness, display, and chase during courtship), stress response (peak metabolic rate), and coloration (black spot, fuzzy black, and orange). The lack of correlation of any behavior or metabolism with black coloration indicates that the melanocortin hypothesis is not supported in this species. However, we observed covariation among coloration traits, as well as among behavioral traits. Our findings suggest that, although there appear to be constraints within sets of related traits, coloration, physiology, and behaviors can potentially evolve as independent modules in response to selection in this species. Abstract : Variation in black coloration between male guppies is not correlated with variation in behaviors or metabolism. We tested the melanocortin hypothesis predicting that such correlations can arise through a common genetic pathway. We conclude that instead these traits are not linked; thus, they can potentially evolve independently from each other.